Answer:
x=-3 or x=-1
Step-by-step explanation:
Subtract 3 from both sides of your equation, it should look like this |3x+6|+3-3=6-3.
Simplify to get |3x+6|=3
Apply the absolute rule to get 3x+6=-3 or 3x+6=3.
3x+6=-3 : x=-3
3x+6=3 : x=-1
I'm glad I was able to help have a great day!
First, you plot the coordinates to visualize the problem clearly. As you can see in the picture, the longest sides could either be one of those marked in red. This could be initially determined when you use visual estimation. We measure this using the distance formula: d = √[(x2-x1)^2 + (y2-y1)^2)]
Between coordinates (0,3) and (3,6)
d = √[(3-0)^2 + (6-3)^2)]
d= 4.24 units
Between coordinates (2,1) and (5,4)
d = √[(5-2)^2 + (4-1)^2)]
d= 4.24 units
They are of equal length. Both are the longest sides which measures
4.24 units.
The two teachers have 16 and 64 homework papers to return, totalling in 80.
They also have 14 and 60 quizzes to return, totalling in 74.
The ratio of homework papers to quizzes that need to be returned is 80:74